Long-term Study of the 2020 Magnetar-like Outburst of the Young Pulsar PSR J1846-0258 in Kes 75 - R. Sathyaprakash; N. Rea; F. Coti Zelati; A. Borghese; M. Pilia; M. Trudu; M. Burgay; R. Turolla; S. Zane; P. Esposito; S. Mereghetti; S. Campana; et al. (The Astrophysical Journal)
Magnetar-like activity has been observed in a large variety of neutron stars. PSR J1846−0258 is a young 327 ms radio-quiet pulsar with a large rotational power (∼8 × 10 ^36 erg s ^−1 ), and resides at the center of the supernova remnant Kes 75. It is one of the rare examples of a high-magnetic-field pulsar showing characteristics both of magnetars and radio pulsars, and can thus provide important clues on the differences in the emission mechanisms between these two classes. In 2006, PSR J1846−0258 was detected to undergo an outburst for the first time, accompanied by a large flux increase, millisecond X-ray bursts, significant spectral changes, and a large timing glitch. In the period between 2020 May and June, after 14 yr of quiescent stable emission, the source underwent a second magnetar-like outburst, which was followed up with several observations by Neutron Star Interior Composition Explorer, XMM-Newton, NuSTAR, and Swift. In this work, we report on the long-term timing and X-ray spectral properties of the source following the 2020 outburst, and place upper limits on any source activity at radio wavelengths. We demonstrate that the pulsed flux increased by a factor >6 during the outburst, followed by nontrivial variability in the spin-down rate. Our timing analysis shows that the spin frequency and its derivative are clearly affected by magnetospheric activity due to the outburst. We find hints for an oscillation in the frequency derivative with a timescale of 50–60 days, recovering later on to stable quiescence.